DNA damage and mutation. Types of DNA damage - Stoyan Chakarov (BioDiscovery, 2014)
This review outlines the basic types of DNA damage caused by exogenous and endogenous factors, analyses the possible consequences of each type of damage and discusses the need for different types of DNA repair. The mechanisms by which a minor damaging event to DNA may eventually result in the introduction of heritable mutation/s are reviewed. The major features of the role of DNA damage in ageing and carcinogenesis are outlined and the role of iatrogenic DNA damage in human health and disease (with curative intent as well as a long-term adverse effect of genotoxic therapies) are discussed in detail.